359 Prevalence of Allergic Conjunctivitis in Childhood - Geraldini, Marcos (World Allergy Organization Journal, 2012)
BACKGROUND: The prevalence of allergic conjunctivitis (AC) has not been established. Estimates suggest that ocular allergies affect 15 to 20% of the worldwide population yet most epidemiological studies encompasses nasal and ocular allergy symptoms together and have not been specific with respect to AC. The aim of this study was to verify the prevalence of ocular allergy symptoms in adolescents. METHODS: Adolescents were selected from a sample of schools and self-completed in classrooms a previously validated questionnaire on symptoms of AC. AC was considered when more than 3 episodes of ocular itching were reported in the past 12 months. Related symptoms as tearing, photophobia, foreign body sensation, impact on daily activities, and diagnosis of allergic conjunctivitis were analyzed. RESULTS: Questionnaires from 3120 adolescents (mean 13.3 ± 1.1 years) were analyzed. Ocular itching in the past 12 months occurred in 1,592 (51%). The most frequent associated symptom was tearing (74%) followed by photophobia (50.1%) and foreign body sensation (37.1%). The prevalence of allergic conjunctivitis was 20.7% affecting more females (56.1% vs 45.9%; P < 0.01). Moderate and severe interference in daily activities were reported by 66% and 21%, respectively. Diagnosis of AC was reported by 47% of them. CONCLUSIONS: Symptoms of ocular allergy are common and cause great impact on daily activities in adolescents. Accessing risk factors and the allergic status of these patients should be the focus of future epidemiological studies on AC.